2005
DOI: 10.1289/ehp.7111
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Trihalomethane Concentrations in Public Water Supplies to Stillbirth and Birth Weight in Three Water Regions in England

Abstract: We investigated the association between total trihalomethanes (TTHMs) and risk of stillbirth and low and very low birth weight in three water regions in England, 1992–1998; associations with individual trihalomethanes (THMs) were also examined. Modeled estimates of quarterly TTHM concentrations in water zones, categorized as low (< 30 μg/L), medium (30–59 μg/L), or high (≥60 μg/L), were linked to approximately 1 million routine birth and stillbirth records using maternal residence at time of birth. In one regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 58 publications
1
70
0
3
Order By: Relevance
“…Several studies also reported positive associations between THM concentrations and a number of adverse reproductive effects, particularly stillbirth and low weight for gestational age [25,26]. However, as better studies were carried out these were increasingly negative and evidence started to emerge of confounding factors.…”
Section: Chemicals Arising From Drinking Water Treatmentmentioning
confidence: 99%
“…Several studies also reported positive associations between THM concentrations and a number of adverse reproductive effects, particularly stillbirth and low weight for gestational age [25,26]. However, as better studies were carried out these were increasingly negative and evidence started to emerge of confounding factors.…”
Section: Chemicals Arising From Drinking Water Treatmentmentioning
confidence: 99%
“…Quanto maior o tempo de contato da maté-ria orgânica com o cloro, maior a produção de trialometanos 5 . Vários estudos [6][7][8][9][10] têm demonstrado uma associação entre a presença de trialometanos na água de abastecimento, em concentrações que variam entre 80 e 100µg/L, e efeitos na saúde da população. Também tem-se focalizado a relação entre a concentração de trialometanos e efeitos adversos no aparelho reprodutor, bem como no desenvolvimento fetal.…”
Section: Introductionunclassified
“…However, formation of chlorinated byproducts such as trihalomethanes (THMs) that are recognized to cause adverse health effects is of great concern. [1,2] Besides the employment of advanced oxidation processes such as ozonation, photocatalytic oxidation, and Fenton reaction for oxidative degradation, the chlorinated byproducts could be alternatively reduced to their nonchlorinated analogues [3] with less toxicity and better biodegradability.…”
Section: Introductionmentioning
confidence: 99%